2018
DOI: 10.1002/jmri.26032
|View full text |Cite
|
Sign up to set email alerts
|

Utility of volumetric contrast‐enhanced and diffusion‐weighted MRI in differentiating between common primary hypervascular liver tumors

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;48:1080-1090.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
(93 reference statements)
1
6
0
Order By: Relevance
“…This restriction is substantially lower than in malignant lesions, but the difference may not be noticeable to naked eye in DWI/ADC evaluation. In their recent study, Zarghampour et al, reported that ADC is successful in HA-HCC and HA-FNH differentiation while being unsuccessful in FNH-HCC differentiation [23]. Similar to the mentioned study, our study found that ADC is unsuccessful in FNH-HCC differentiation.…”
Section: Original Articlesupporting
confidence: 88%
“…This restriction is substantially lower than in malignant lesions, but the difference may not be noticeable to naked eye in DWI/ADC evaluation. In their recent study, Zarghampour et al, reported that ADC is successful in HA-HCC and HA-FNH differentiation while being unsuccessful in FNH-HCC differentiation [23]. Similar to the mentioned study, our study found that ADC is unsuccessful in FNH-HCC differentiation.…”
Section: Original Articlesupporting
confidence: 88%
“…Various imaging modalities have been applied in the distinction between HCC and FNH, such as CT [1,9,10], Doppler ultrasound [11,12] and MRI [1,3,5,[13][14][15]. In previous studies, the gadoxetic acid-enhanced MRI is being increasingly used in differentiating focal liver lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by Shankar, 23 Galea, 31 and Saito 47 reported that DWI has limitations for evaluating the differentiation between HCC/liver lesion grades because the tumor grade does not significantly change the ADC values. Furthermore, Sutherland 48–50 concluded that using DWI to differentiate between solid benign and malignant lesions and different sorts of hypervascular hepatic lesions remains challenging because the differences in ADC values were not statistically significant. For example, Sutherland reported an overlap between the cellularity of focal nodular hyperplasia and malignant liver lesions in low ADC values 48 …”
Section: Diffusion‐weighted Image–magnetic Resonance Imagingmentioning
confidence: 99%